Confronting history : a memoir - Mosse, George L. (George Lachmann), 1918-1999 (Madison : University of Wisconsin, 2000)
Just two weeks before his death in January 1999, George L. Mosse, one of this century's great historians, finished writing his memoir, a fascinating and fluent account of a remarkable life that spanned three continents and many of the major events of the twentieth century. Writing about the events of his life through a historian's lens, Mosse gives us a personal history of our century. This is a story told with the clarity, passion, and verve that entranced thousands of Mosse's students and that countless readers have found, and will continue co find, in his many scholarly books. Confronting History describes Mosse's opulent childhood in Weimar Berlin; his exile in Parts and England, including boarding school and study at Cambridge University; his second exile in the U.S. at Haverford, Harvard, Iowa, and Wisconsin; and his extended stays in London and Jerusalem. Mosse also deals with matters of personal identity. He discusses being a Jew and his attachment to Israel and Zionism. He addresses has gayness, his coming out, and his growing scholarly interest in issues of sexuality. This touching memoir, sometimes harrowing, often humorous, is guided in part by Mosse's belief that "what man is, only history tells, " and by his constant themes of the fate of liberalism, the defining events that can bring about the generational political awakenings of youth (from the anti-fascism struggles of the 1930s to the campus anti-war movement of the 1960s, the meanings of masculinity and racial and sexual stereotypes, the enigma of exile, and -- most of all -- the importance of finding one's self through the pursuit of truth, and through an honest and unflinching analysis of one's place in the context of his times
TABLE OF CONTENTS -- Introduction: on native ground -- The setting -- Family matters -- Building character in Salem -- Experiencing exile -- Political awakenings -- Gaining a foothold -- The Iowa years -- Finally home -- Confronting history -- Journey to Jerusalem -- Excursus: London as home -- The past as present
Keywords: Mosse, George L. -- 1918-1999; Historians -- United States -- Biography; Historians -- United States -- Biography; Autobiography; Autobiographies